PENENTUAN JUMLAH PRODUKSI BAJU BATIK DI BATIK MERAK MANIS DENGAN METODE FUZZY MAMDANI - Dwi Rudi Setiawan; kustanto kustanto; Yustina Retno Wahyu Utami (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2019)
Determination of production is one of the important activities within a company because it affects the production process that requires careful calculation. At this stage, the problem will arise because of the uncertainty in the determination of production. Fuzzy logic is one method to analyze a system that contains uncertainty. In this research used the Mamdani method or known as Min-Max method. The purpose of this research is to build the application of the determination of the number of batik clothes production using Fuzzy Mamdani method. The variables used there are 3 namely: demand, inventory, and production. Data collection method used observation method, interview and literature study. The method to design the application system is DFD (Data Flow Diagram), ERD (Entity Relationship Diagram). The proposed system is developed using MySQL and PHP. The result of this research is an application to calculate the production amount of batik clothes, especially in Batik Merak Manis. Based on the results of 20 sample data obtained level performance of 99.51%.Keywords: Fuzzy Mamdani, Batik clothing products, Determination.